2006
DOI: 10.1111/j.1468-0386.2006.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhetoric or Reality? ‘New Governance’ in EU Environmental Policy

Abstract: When scrutinising the literature on EU environmental policy, it becomes apparent that there has been a comprehensive transition in underlying governance ideas during the last two decades. At the core of these changes is the abolition of traditional patterns of interventionist command-and-control regulation in favour of economic instruments and 'context-oriented' governance. In view of these developments, this article has two objectives: first, it looks into which causes and factors initiated these discussions;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(20 citation statements)
references
References 7 publications
(7 reference statements)
2
13
0
1
Order By: Relevance
“…Gunningham and Grabosky 1998). For example, Jordan et al (2005) found that there was little evidence that NEPIs were replacing traditional tools; instead co-existence seemed to be the most prevalent pattern in European environmental policy (see also Holzinger et al 2006). This finding was very much confirmed by Holzinger et al (2009, pp.…”
Section: Instruments Government and Governancesupporting
confidence: 73%
“…Gunningham and Grabosky 1998). For example, Jordan et al (2005) found that there was little evidence that NEPIs were replacing traditional tools; instead co-existence seemed to be the most prevalent pattern in European environmental policy (see also Holzinger et al 2006). This finding was very much confirmed by Holzinger et al (2009, pp.…”
Section: Instruments Government and Governancesupporting
confidence: 73%
“…For examples of domestic New Governance, seeFreeman (1997-98);Trubek and Trubek (2007);Holzinger et al (2006);Coglianese et al (2003).…”
mentioning
confidence: 99%
“…The EU has also aspired to be a global environmental leader, although many have noted a growing mismatch between the EU's pronouncements and its limited capacity to deliver (Chaban et al 2006;Holzinger et al 2006). Using the distinction introduced by Andresen and Agrawala (2002), the question is whether the EU is in fact a leader or a 'pusher' characterized by persistent but largely ineffectual negotiating efforts and public declarations.…”
Section: European Unionmentioning
confidence: 99%